Population structure and genetic diversity of Streptococcus suis isolates obtained from the United States - Nicholson, Tracy L.; Kalalah, Anwar A.; Eppinger, Mark (Frontiers in Microbiology, 2023)
Diseases caused by the zoonotic pathogen Streptococcus suis are an extensive economic problem as well as an animal welfare concern for the global swine industry. Previous studies have evaluated the genomic diversity and population structure of S. suis isolates, however, the majority of these studies utilized isolates obtained from countries other than the U.S. This study applied whole genome sequencing and cgMLST-based typing to evaluate the population structure and genetic relatedness among S. suis isolates obtained within the U.S. The established high-resolution phylogenomic framework revealed extensive genomic variation and diversity among the sampled S. suis isolates, with isolates from the U.S. and from countries outside the U.S. found interspersed in the phylogeny. S. suis isolates obtained within the U.S. did not cluster by state or geographic location, however, isolates with similar serotypes, both obtained from within and outside the U.S., generally clustered together. Average nucleotide identity (ANI) values determined for the S. suis genomes were extensively broad, approaching the recommended species demarcation value, and correlated with the phylogenetic group distribution of the cgMLST-based tree. Numerous antimicrobial resistance (AMR) elements were identified among both U.S. and non-U.S. isolates with ble, tetO, and ermB genes identified as the most prevalent. The epf, mrp, and sly genes, historically used as markers for virulence potential, were also observed in the genomes of isolates that grouped together forming a subclade of clonal complex 1 (CC1) isolates. Collectively, the data in this report provides critical information needed to address potential biosurveillance needs and insights into the genetic diversity and population structure of S. suis isolates obtained within the U.S.